Senior high school students' preference and reasoning modes about nuclear energy use - Yang, Fang-Ying (International journal of science education, 2003)
This study examined senior high school students' cognitive orientation toward scientific or social information, designated as information preference, and associated preferential reasoning modes when presented with an environmental issue concerning nuclear energy usage. The association of the information preference variable with some academic and personal background attributes of the participants was also examined. A questionnaire, preference survey test and interview methods were used to gather the data. Students' preference test scores fell within m0.66 to 2 on a scale of m4 (social orientation) to 4 (scientific orientation). Statistical analyses showed that students' performance in science was a good predictor of the information preference exhibited by students. Interview content analysis showed that students' preferences and reasoning modes were mutually consistent. Particularly, subjects of neutral preference, whose preference scores fell between 0 and 1, displayed a reasoning mode that is considerably integrated containing references to both scientific and socially relevant content.